Serang Javanese Speech Contest at SMK Global 2 Bandung to Preserve the Use of Serang Javanese - Sairoh, Lisa; Junedi, Beni; Sulistiawati; Putriani; Rohmayanti; Hartono, Dedi (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
Language is one of the essential abilities that humans have to communicate, both between speakers and listeners, because humans are social creatures who interact with each other. In Indonesia, the use of regional languages is very diverse, with more than 700 existing regional languages, for example Banten Javanese. Banten Javanese is the result of a meeting between Demak Javanese, Cirebon Javanese, and Sundanese spoken by Banten natives when the Sultanate of Banten was formed in 1525. Over time, the Serang Javanese language began to fade. Although not yet comprehensive, in certain places, for example at SMK T 2 Global, activities have begun to be carried out that aim to preserve the Serang Javanese language. This article is presented through literature and interview methods. Bebasan Javanese language can be said to have begun to lead to extinction due to several causal factors, namely parents not teaching their children and Serang Javanese language is also considered difficult in terms of vocabulary and pronunciation. Keywords: speech competition, cultural contest, Serang javanese